Trailer K-Drama Moving dan Minat Menonton K-Drama di Disney+ Hotstar - Rahmadani, Ririn; Abidin, Zainal; Utamidewi, Wahyu (Jurnal Ilmiah Wahana Pendidikan, 2025)
The K-Drama "Moving" which is broadcast in August 2023, has received a lot of attention from K-Drama fans and has achieved extraordinary popularity. The purpose of this research is to investigates the influence of the k-drama Moving’s trailer on viewer’s interest in watching the entire series on Disney+ Hotstar. The theory used in this research is uses and gratifications theory, which assume that audiences actively select media to fulfill their needs. This research employs a quantitative explanatory research method to explain the relationship and impact between the variables. The findings reveal that the Intensity variable does not influence on the interest in watching the k-drama on Disney+ Hotstar with an influence value of -1.55%. In contrast, the Message Content and Attraction variables demonstrate a significant influence on viewers' interest in watching the k-drama on Disney+ Hotstar with influence values ​​for each variable of 9.59% and 31.82%.